276 ROLE OF C-REACTIVE PROTEIN AS AN ADJUVANT DIAGNOSTIC AND PROGNOSTIC MARKER IN PATIENTS UNDERGOING STRESS TEST FOR RISK STRATIFICATION AND IN PATIENTS WITH STABLE CORONARY ARTERY DISEASE. (1st January 2005) - Banuru, S.; Perumandla, S.; Guttigoli, A.; Abraham, M.; Khanna, A.; Niranjan, S.
Abstract : Background: Elevation of C-reactive protein (CRP) is a marker of adverse outcomes in acute coronary syndromes (ACS). Its role has not been evaluated in patients with stable coronary artery disease (CAD) and in those who are undergoing stress test for risk stratification. We hypothesized that patients with a positive stress test are more likely to have higher CRP levels than patients with a negative stress test. Methods: Patients who underwent stress test for CAD evaluation or risk stratification had a CRP level drawn prior to the stress test after an informed consent was obtained. The lower limit of CRP is 0.5 at our institution and the test is of intermediate sensitivity. The stress test was performed as per clinical indication and at the attending cardiologist's discretion. Patients underwent either exercise or pharmacological stress nuclear SPECT test. Results: Total of 93 patients' results were available for analysis. CRP was positive in 7 out of 0 patients with positive stress test. CRP values being 0.6, 0.7, 0.9, 0.9, 1.6, 2.8, and 3.0 with a mean of 1.5. The patient with highest CRP value died of acute coronary event ten days after the stress test. Only 2 patients who had a positive stress test had negative CRP levels. CRP levels were positive in 7 out of 84 patients who had a negative stress test. The CRP values were 0.6, 0.6, 0.6, 0.6, 0.6, 0.7, and1.2 with a mean of 0.7. Two patients with positive CRP levels in the negative stress test group (including the patient with level of 1.2) had an episode of angina pectoris one week prior to the test. The sensitivity for the test was 77.8% and the specificity was is 91.4% to predict a positive stress test. Conclusions: CRP is a valuable prognostic marker even in patients with stable CAD and in those undergoing risk stratification and can be used as an additional marker in predicting adverse outcomes in patients with stable coronary artery disease. It is complementary to nuclear stress test and can help in identifying high-risk patients who would benefit from aggressive interventions in their management. In patients who had a negative stress test and positive CRP values the values of CRP are low.